PENGARUH FAKTOR FUNDAMENTAL DAN RISIKO SISTEMATIK TERHADAP HARGA SAHAM PERUSAHAAN DI PASAR MODAL SYARIAH (Studi Kasus di Jakarta Islamic Index Periode 2014-2017) - Vega Zahrah Narendra Duhita; Nisful Laila (Universitas Airlangga, 2019)
This research aims to find out and explain the influence of financial fundamental factors (DER, NPM, ROA, TATO, EPS, and PER) and systematic risks (Stock Beta) on stock price of the companies which were registered on Jakarta Islamic Index period 2014-2017. It uses quantitative approach to find out the relation between one variable and another. Data used is a secondary data including the value of every ratio used and closi stock price in ecery company. The object of the research is 16 companies which were registered on Jakarta Islamic Index during the research period. This research focuses on whether the variables used affect companies’ stock price by using multiple linier regression test and statistical tool IBM SPSS 25 and determining the level of significance 5%. The results of the research show that the fundamental factors and systematic risks simultaneously have a positive and significant effect on companies’ stock price on JII during period 2014-2017. Meanwhile, the variables of DER, ROA, TATO, EPS partially have a positive and significant effect, the variables of NPM, PER, and stock beta have insignificant effect on companies’ stock price on JII during period 2014-2017.Keywords: Fundamental Analysis, Stock Price, Systematic Risks, Jakarta Islamic Index